Changes in hemispheric dominance following targeted muscle reinnervation: a case study - Mootaz AboElnour, Toka; Fraser Wilsey, Kaitlin; Yang, Kai; Borrell, Jordan Alexander; Zuniga, Jorge (Frontiers in Human Neuroscience, 2025)
Phantom limb pain (PLP) after amputation is a multifaceted condition. Targeted muscle reinnervation (TMR) surgery coapts amputated nerves to motor nerves of regional muscles, closing the neuromuscular loop, enabling improved myoelectric prosthesis control and reducing PLP. Long-term effects of TMR and residual limb use have been observed; however, the short-term neural changes and their timeline are not understood. The purpose of this study was to examine the cortical changes shortly after TMR without a prosthesis, specifically the functional connectivity and hemispheric dominance during a motor task involving the affected limb. The case participant is a male 52 years old, with a left traumatic transradial amputation sustained 4 years earlier, scheduled for TMR surgery. Data was collected before and 2 months after TMR. Brain activity was recorded using functional near-infrared spectroscopy (fNIRS) while the participant performed a gross manual dexterity task (box and block test) using their phantom hand. Pain levels were assessed using a 10-point visual analog scale (VAS). Following TMR, the participant reported a VAS score of 0 and increased use of the amputated limb in daily activities. fNIRS analysis during the affected limb task showed a reduction in interhemispheric functional connectivity, prominently in the primary sensory cortex, where the average z-value decreased from 0.29 to 0.12 after TMR. In contrast, connectivity between the premotor and supplementary motor areas increased slightly, from 0.08 to 0.12. Overall, intrahemispheric correlations decreased, with opposite patterns observed across hemispheres. The largest changes occurred ipsilaterally: connectivity between the primary motor and sensory areas increased from 0.23 to 0.27, while contralaterally it decreased from 0.22 to 0.16. Conversely, connectivity between the primary motor and premotor areas increased contralaterally but decreased ipsilaterally. Hemispheric dominance calculated through the Laterality index (LI) shifted from bilateral (LI = 0.079) to ipsilateral (LI = 0.59), primarily driven by reduced activation in the contralateral primary motor cortex. These findings suggest that TMR alone can elicit measurable cortical changes in the early post-surgical period, alongside improvements in pain and functional limb use. They also support fNIRS as a non-invasive method for monitoring neural adaptation after TMR and enhance understanding of PLP mechanisms and recovery timelines.